ALVIN AND THE CHIPMUNKS FILM AS A TEACHING MEDIA TO IMPROVE STUDENTS’ ABILITY IN SPOKEN NARRATIVE TEXT: A CASE OF TENTH GRADE STUDENTS OF SMA NEGERI 1 GUBUG - Amelia Jenri Fourtina (ETERNAL (English Teaching Journal), 2014)
This final project focuses on Alvin and the Chipmunks film in spoken narrative text to improve students’ speaking skill. The objectives of this study are (1) to find out the students’ speaking ability before being taught by using Alvin and the Chipmunks film in spoken narrative text, (2) to find out the students’ speaking ability after being taught Alvin and the Chipmunks film in spoken narrative text, and (3) to find out whether or not there is significant difference of the students’ speaking ability before and after being taught using Alvin and the Chipmunks film at storytelling. In this study, the population was the tenth grade students of SMA Negeri 1 Gubug in the academic year 2013/2014. The number of the population was 324 students classified into 9 classes. Cluster sampling is used in taking the sample. 69 students are selected as sample out of 324 students that consist of 36 students from class Xi as the experiment group and 33 students XH as the control group. Experiment research was used here to get the data. The pre-test is given to the students on both of groups. After that, the difference treatments are given in experimental group. At the end of the research, the post-test is given to both of groups. In experiment group, the students retell the story of Alvin and the Chipmunks after watching the film and in control groups the students retell without watching the film in front of the class. The mean score of the experiment group 72.08 was higher than the mean score of the control group 65.455. The t-test application to the scores of two groups showed that the valuable (9,67) is higher than t-table (1.996). It can be seen that there is a significance difference speaking ability of the tenth grade students of SMA N 1 Gubug after being taught using Alvin and the Chipmunks film. To overcome these problems, the researcher offers some suggestions. For the school, the school should give good facilities and many media for teaching and learning process. For the teacher, the teacher should give variation teaching especially using media in spoken narrative text to improve students’ speaking skill. For the students, the students have to do more active, confident, and practice to practice speaking English